The contemporary lives of age-old tales : characters, contexts, and critical issues - Mathis, Janelle (Array, 2019)
Aligned with the sociocultural nature of traditional tales and other folk literature of the Western world, this study examines three picturebooks to consider the significance of contemporary retellings of traditional tales. A critical content analysis approach to text and images employs select tenets of a particular theory for each book inclusive of childism, post-colonial, and archetype theories. The findings relate each book to current sociocultural issues: the agentic child in building community; colonial and post-colonial understandings; and identity, stereotypes, and archetypes. Additionally, environmental themes are woven through each. The findings support the ongoing significance of these living folktales for personal and community development as they connect intertextually across eras and national cultures.